Copper and iron mediated growth of surfactant‐free PtCu and PtFe advanced electrocatalysts for water oxidation and oxygen reduction. Issue 2 (25th March 2021) - Zhang, Ling; Li, Lin; Shi, Yuhe; Wu, Fengxia; Xu, Yan; Zhou, Tingting; Niu, Wenxin; Zhang, Jiaheng; Xu, Guobao
Abstract: Pt‐based alloy nanoparticles are critical electrochemical catalysts for the water oxidation and oxygen reduction reactions. But the surfactants adsorbed on the nanoparticles' surfaces are hard to remove off, blocking the catalytic active sites and decrease the catalysis activity of the alloy catalysts. Herein, we engineered surfactant‐free PtCu alloy polyhedral nanospheres with foam‐like surfaces in pure water at 40°C directly. Metal precursors were reduced by ascorbic acid. The sizes of polyhedral nanospheres were formed by assembling of tiny PtCu alloy nanoparticles in the sizes of 4.2 ± 0.70 nm, resulting the larger nanospheres in the sizes of 124 ± 30 nm. Underpotential deposition of copper atoms occurred, which catalyzed reductions of Pt precursor and depositions of Pt atoms, high yields of Pt component in PtCu alloy nanospheres and fast reaction rate for reductions of Pt precursors were achieved. Common transition metal, Fe, Co, Ni was also investigated. Only Fe atoms were alloyed with Pt crystals, but the contents of Fe were lower than those of Cu in PtCu alloy. Due to the alloyed structures and special surface structures, PtFe and PtCu exhibited 12.8% and 87% higher current densities toward water oxidation reaction and oxygen reduction reactions in acidic medium than those of commercial Pt black, respectively. This work provides us a new way to get surfactant‐free PtM (M = Cu, Fe, etc) alloy nanoparticles which were produced in water. It is significant to achieve the advanced electrocatalysts with clean surfaces and high catalytic activities. Abstract : A novel synthetic route to grow surfactant‐free PtCu and PtFe advanced alloy catalysts in water was found.